Accessibility and Daily Cigarette Consumption among Indonesian Adolescents: A Descriptive Study - Lathifah, Noviana; Rachman, Istiqomah Hanifah; Isnaini, Anisa; Simatupang, Gloria Threesia Piliphinsa (Journal of Indonesian Health Policy and Administration, 2026)
Despite restrictive regulations, Indonesia faces a high prevalence of adolescent smoking, facilitated by easy access to tobacco products. This descriptive study aims to describe cigarette accessibility patterns and daily consumption trends among Indonesian adolescents. A cross-sectional study was conducted using secondary data from the 2019 Global Youth Tobacco Survey (GYTS) involving 9,208 respondents. Descriptive analysis was performed to examine the distribution of age at smoking initiation, daily cigarette consumption, and purchasing accessibility. The majority of respondents started smoking at ≥14 years of age. Daily cigarette consumption showed an increasing trend with age, with older adolescents more likely to consume more than five cigarettes per day. Regarding accessibility, 10.78% of adolescents reported purchasing single cigarettes, and 12.27% were not refused purchase by vendors despite being underage. Overall trends indicate that greater ease of access is associated with increasing age and smoking intensity. Access to cigarettes remains largely unimpeded for Indonesian adolescents, contributing to higher consumption patterns as they age. Strict enforcement of regulations prohibiting cigarette sales to minors is therefore imperative.